Slavery and colonialist evil – Seen & not seen – In today’s brazilian society: For a social pride - Gonçalves, Marcus Fabiano; Oliveira, Terezinha Azevedo (Seven Editora, 2024)
This article will seek to raise a bibliographic reference on the social inequalities verified in Brazil in contemporary times. This theme is embodied in the book entitled Pathways to Recognition, Equality and Respect, by Jacques D’Adesky (2018). The common thread of this work brings reflections aimed at revisiting the past to launch us, at the same time, into questions about the future of race relations in Brazil and in the contemporary world with a view to broadening the debate about the limits of colonial practices and racism for the future of humanity and for the populations subordinated in their identities and cultural values. From this perspective, the questions raised in this study focus on race relations in Brazil in dialogue with the reflections elaborated by Brazilian black activism, namely: is there really equality of opportunity, principles of non-discrimination and merit in the face of affirmative action policies? Are such political practices effective in fostering equal opportunities, recognition and combating racism in contemporary times? DOI:https://doi.org/10.56238/sevened2024.007-008